2024
DOI: 10.1039/d3gc02976j
|View full text |Cite
|
Sign up to set email alerts
|

Used tissue paper as a 3D substrate for non-enzyme glucose sensors

Zhiyu Chen,
Lei Li,
Xuanyu Xiao
et al.

Abstract: Used tissue paper was recycled as the template of the sensor by a green method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…These sensors can synthesize special electrocatalytically active media to catalyze Glu directly. Non-enzymatic CGM biosensor catalysts focused on the development of various nanomaterials, including noble metals such as Au and Pt, 6,154–157 metal oxides such as CuO and Co 3 O 4 , 158–161 and their carbon nanomaterials. 162,163 The main advantage of the non-enzymatic sensor is the increased stability of the sensor and reduced maintenance costs, allowing continuous monitoring of Glu fluctuations without the need to replace the sensor.…”
Section: The Principle Of Bioelectrochemical Glu Sensingmentioning
confidence: 99%
See 4 more Smart Citations
“…These sensors can synthesize special electrocatalytically active media to catalyze Glu directly. Non-enzymatic CGM biosensor catalysts focused on the development of various nanomaterials, including noble metals such as Au and Pt, 6,154–157 metal oxides such as CuO and Co 3 O 4 , 158–161 and their carbon nanomaterials. 162,163 The main advantage of the non-enzymatic sensor is the increased stability of the sensor and reduced maintenance costs, allowing continuous monitoring of Glu fluctuations without the need to replace the sensor.…”
Section: The Principle Of Bioelectrochemical Glu Sensingmentioning
confidence: 99%
“…5b). 6 Unfortunately, this work did not further evaluate the sensing performance of live animals. In fact, among the many non-enzymatic CGMs, only very few studies have reported sensing results in animals.…”
Section: The Principle Of Bioelectrochemical Glu Sensingmentioning
confidence: 99%
See 3 more Smart Citations